ChemInform Abstract: Syntheses of Two Vanadium Oxide—Fluoride Materials that Differ in Phase Matchability. Issue 15 (April 2015) - Donakowski, Martin D.; Gautier, Romain; Lu, Hongcheng; Tran, T. Thao; Cantwell, Jacqueline R.; Halasyamani, P. Shiv; Poeppelmeier, Kenneth R.
Abstract Non‐centrosymmetric NaVOF4(H2O) (I) and NaVO2‐xF2+x (II; x = 1/3) are prepared from an 1:1:4 molar mixture of V2O5, NaCl, and HF (teflon container, 100 °C, 30 min for (I) and 150 °C, 24 h for (II)).